2020
DOI: 10.1186/s12885-020-07256-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of curcumin in enhancing cancer therapy: A systematic review

Abstract: Background: Curcumin is herbal compound that has been shown to have anti-cancer effects in pre-clinical and clinical studies. The anti-cancer effects of curcumin include inhibiting the carcinogenesis, inhibiting angiogenesis, and inhibiting tumour growth. This study aims to determine the Clinical effects of curcumin in different types of cancers using systematic review approach. Methods: A systematic review methodology is adopted for undertaking detailed analysis of the effects of curcumin in cancer therapy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
146
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(174 citation statements)
references
References 82 publications
0
146
0
1
Order By: Relevance
“…In light of the myriad of preclinical cancer prevention efficacy data, that there are no studies in the pipeline pursuing meaningful clinical cancer prevention endpoints via RCTs is somewhat disappointing. Mansouri et al [59] recently published a systematic review investigating the effects of curcumin on cancer therapy, collating evidence which suggests that curcuminoids are able to alleviate side effects of chemo-or radio-therapy with concurrent improvement of quality of life. This study, taken together with the evidence presented here, gives some credence to potential beneficial effects of curcumin use in pre-cancerous conditions, and for radio-toxicity prevention in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the myriad of preclinical cancer prevention efficacy data, that there are no studies in the pipeline pursuing meaningful clinical cancer prevention endpoints via RCTs is somewhat disappointing. Mansouri et al [59] recently published a systematic review investigating the effects of curcumin on cancer therapy, collating evidence which suggests that curcuminoids are able to alleviate side effects of chemo-or radio-therapy with concurrent improvement of quality of life. This study, taken together with the evidence presented here, gives some credence to potential beneficial effects of curcumin use in pre-cancerous conditions, and for radio-toxicity prevention in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various chemodietary agents and nutraceuticals have been shown to be effective against several types of cancers and infectious diseases [17][18][19][20][36][37][38]. Among these, curcumin has been tried as adjuvant therapy in clinical studies to treat various conditions largely for cancers [39][40][41]. Curcumin has also been shown to possess anti-HIV activity [19,20,42].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a yellow pigment that is considered to be the active ingredient of turmeric, a flowering plant of the ginger family with the scientific name of Curcuma longa [ 5 ]. It is best known in its turmeric powder form as a spice used in curry (Figure 5) and is a polyphenol with proven anti-inflammatory properties [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin-induced side effects were reported to be restricted to gastrointestinal upset, while hematologic adverse events, like neutropenia, were not encountered. A recent review by Mansouri et al demonstrated that cancer patient survival rates were increased and their chemotherapy symptoms were reduced, depending on the dose of curcumin they received in curcumin-involving CTs of those patients [ 5 ]. Granted, previous studies on curcumin were conducted using regulated curcumin capsules, a study by Bayet-Robert, for example, prescribed a maximum dose of 8 g per day for seven days per each docetaxel treatment cycle, finding 6 g to be the maximal tolerable dose [ 15 ].…”
Section: Discussionmentioning
confidence: 99%